2008
DOI: 10.1007/s10606-008-9075-6
|View full text |Cite
|
Sign up to set email alerts
|

Social Loafing in Technology-Supported Teams

Abstract: This study examines the occurrence of social loafing in technology-supported teams along with methods for diminishing loafing. A controlled laboratory experiment with a 3×2×2 factorial design is used. The independent variables -feedback, anonymity, and group size -are manipulated experimentally. It was expected that social loafing -a widely observed phenomenonwould indeed occur in technology supported teams. It was also expected that the traditional means of reducing social loafing (i.e., identifiability and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 19 publications
2
35
0
Order By: Relevance
“…They concluded that smaller subunits perform better than their larger counterparts. These findings are consistent with the social science literature suggesting that "social loafing" may occur in larger groups (Latané et al, 1979;Suleiman and Watson, 2008). Social loafing is a well-known phenomenon that documents the decrease of individual effort when individuals work in groups (Latané et al, 1979).…”
Section: Optimal Work Group Sizesupporting
confidence: 89%
“…They concluded that smaller subunits perform better than their larger counterparts. These findings are consistent with the social science literature suggesting that "social loafing" may occur in larger groups (Latané et al, 1979;Suleiman and Watson, 2008). Social loafing is a well-known phenomenon that documents the decrease of individual effort when individuals work in groups (Latané et al, 1979).…”
Section: Optimal Work Group Sizesupporting
confidence: 89%
“…Information systems (IS) researchers have devoted considerable attention to the problem of social loafing and productivity loss in technology-supported teams, especially in the context of electronic brainstorming (e.g., [19,28,33,74,92,97,99,104,110]). However, social loafing is not a phenomenon that is confined to brainstorming tasks.…”
Section: Social Loafing In Technology-supported Teamsmentioning
confidence: 99%
“…team Size team size has been the main explanation for social loafing in technology-supported teams [97]. For example, Chidambaram and tung [19] and Valacich et al [101] provided empirical evidence that as team size increases, productivity per person decreases.…”
Section: Social Loafing In Technology-supported Teamsmentioning
confidence: 99%
See 2 more Smart Citations